PENERAPAN SIMULASI PHET KONVERSI ENERGI BERBASIS SAINTIFIK UNTUK MENGUKUR HASIL BELAJAR MAHASISWA PENDIDIKAN FISIKA - Amin, Ahmad; Yuneti, Armi (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2024)
Understanding Physics concepts in the Physics Education Study Program at PGRI Silampari University is very important to support their field of expertise in understanding more complex material. The Mechanics course consists of various abstract concepts, including Energy Conversion material. The use of computer programs such as the PhET Simulation application is very important to explain this abstract material. The aim of this research is to see students' interest in learning after applying Scientific-based PhET media in learning. The method used is the descriptive method, and data analysis uses descriptive analysis regarding interest in learning after implementing the learning. The test subjects in this research were third semester students taking Mechanics courses in the Physics Education Study Program at PGRI Silampari University. The research instrument is a test question consisting of 10 multiple choice questions. The research results obtained by students after applying simulated PhET media reached an average score of 85, with a percentage value of 95%, so it can be said that the application of scientific-based simulated PhET media to energy conversion material can make student learning outcomes considered successful. So it is concluded that after learning using PhET media, student learning outcomes are considered successful.